Nomadyczny projekt Dawida Foenkinosa = Nomadic project of David Foenkinos - Zhukova, Natalia (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The article overviews a nomadic project of postmodernism based on the French novel "Memories" (original title "Les Souvenirs") by David Foenkinos. It is noted that nomadic (from English nomad ? a wanderer) project captures in his text the state of culture being "seized" by the quantum leap principle.
Keywords: wspomnienia; nomada; projekt nomadyczny; postmodernizm; chaosmosis (przestrzeń chaosu); eon; memories; nomad; nomadological project; postmodernism; chaosmosis (chaotic space)